Aspects of a family-friendly employment approach within a hungarian higher education institution - Győri, Zsuzsanna; Juhász, Tímea; Szegedi, Krisztina (Vezetéstudomány / Budapest Management Review, 2023)
Work-life balance has become more important in higher education, due to increasing student numbers, rising expectations and changing regulatory environmental conditions, but little is known about family-friendly employment in academia. This article examines the different approaches to the family-friendly employment approach in the field of Hungarian higher education. After reviewing the relevant literature, the authors conducted 31 in-depth interviews in the largest business and higher education institution in Hungary, involving lecturers, researchers and non-teaching staff of different ages, genders and at different levels of the organizational hierarchy. The results showed that there is no difference by age and position in the assessment of the issue of quality of life, while this can no longer be said about the involvement of work and private life.